Hubungan Kadar HbA1c Dengan Kadar Kolesterol Total Pada Penderita Diabetes Mellitus Tipe 2 Dirumah Sakit Pertemina Bintang Amin HUsada Bandar Lampung 2022. - Indra Saputra; Zulfian; Selvia Anggraeni; Toni Prasetya (Medula, 2022)
Diabetes mellitus (DM) is a chronic metabolic disease due to decreased insulin production in pancreatic cells, or the body experiences insulin ineffectiveness. Based on data from the International Diabetes Federation (IDF), in 2013 – 2017 there was an increase in the number of people with DM from 10.3 million to 16.7 million in 2045. This type of research is an observational analytic with a cross sectional method using a total sampling of 30 patient samples. Type 2 DM that meets the inclusion criteria. Data collection begins in February 2022 until it is completed. The data used are primary data in the form of direct examination. Data were evaluated by chi square test. The research sample was 30 patients with type 2 diabetes with an HbA1c value of 7%, namely 23 patients (76.3%), for an HbA1c value <7%, as many as 7 patients (23.3%) and total cholesterol levels 200mg/dl. namely as many as 20 patients (66.7%), for total cholesterol levels <200mg/dl as many as 10 patients (33.3%). The results of the chi square correlation obtained a value of p = 0.033, because the value of p = 0.033 <0.05 so it can be stated that Ha is accepted and Ho is declared rejected or there is a significant correlation, with p = 0.033 it can be interpreted that the strength of the correlation is positive between the HbA1c value and cholesterol levels. total in patients with type 2 diabetes. There was a significant correlation between the value of HbA1c and total cholesterol levels in patients with type 2 diabetes with p-value = 0.033.